Estrat??gia de terceiriza????o determinada pela an??lise de campos e armas da competi????o - Rylo, Emerson Fernando (2004)
By means of an appropriate classification of companies by its functions (in main functions ??? of production and service ??? support functions and internal service functions), this work deals the outsourcing about several aspects. Initially, is developed one strategy of outsourcing, suggesting a hierarquized process of makeor - buy decisions about what functions outsource and to describe that transferring must be done in three successive stages. The relevant aspect of the work is the presentation of a quantitative methodology, based in camps and arms of competition, to identify in which main functions is the core business of the company. And so, that functions should not be outsourced. The known procedure described in the literature to identify the core business of company have need objectives criteria. The methodology tries to identify manager tools and/or operational better competencies. These tools can give competitive advantage to the company in some camps of competition. This camp is directly associated to main company functions. Also is presented a methodology to identify the others functions, that should not be outsourced, and one study of case in a textile industry, where the model was tested.